MAPPING MULTIPLE BRAND-CELEBRITY CONGRUENCE WITH OVERALS: AN EVIDENCE FOR THE MEANING TRANSFER MODEL - Kutlu, Mustafa Bilgehan (Journal of process management and new technologies, 2022)
This study aims to provide evidence for the meaning transfer model. In Turkey, five apparel retailer brands and five celebrities are evaluated with brand personality and credibility models, respectively via pick any scales. 305 respondents selected with a convenience sampling approach attend the study. In order to compare different types of entities (brands and celebrities) with nominal variables, OVERALS analysis is performed. Associations regarding brands and celebrities are treated as sets of variables in OVERALS analysis. Three out of five brand-celebrity pairs are found to be closely congruent. In the context of multiple brand-celebrity comparisons, this relativistic congruence provides evidence for the meaning transfer model. Moreover, several essential associations in the meaning transfer process (for celebrities sexy, big fan following, and non-controversial public image and for brands stable, responsible, and active) are revealed. Findings of the study and OVERALS analysis are expected to deepen the understanding of the meaning transfer model.